Comparison of Dysfunctional Lens Index and Scheimpflug Lens Densitometry in the Evaluation of Age-Related Nuclear Cataracts - Faria-Correia, Fernando (2016)
To describe the Dysfunctional Lens Index (DLI) from ray-tracing aberrometry and to test its correlations with logMAR corrected distance visual acuity (CDVA) and lens grading based on the Lens Opacities Classification System III (LOCS III) and the Scheimpflug-based lens density.